PEMANFAATAN AUGMENTED REALITY (AR) UNTUK MENINGKATKAN PARIWISATA BUDAYA SEJARAH BABAD PASIR LUHUR DI DESA WISATA TAMANSARI - DEUIS NUR ASTRIDA (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Cultural tourism plays a crucial role in preserving the history and local wisdom of a region. One such heritage site is the Babad Pasir Luhur in Tamansari Tourism Village, Banyumas. However, the delivery of historical information to tourists remains limited and conventional. This study aims to develop and test Augmented Reality (AR) technology as an interactive medium for introducing the history of Babad Pasir Luhur. The method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The research stages include analyzing tourist needs, designing an AR system based on Unity 3D and Vuforia, creating 3D models of historical figures, and testing the application with tourists. The results of the limited trial indicate an increase in interactivity, historical understanding, and cultural tourism appeal through the immersive experience provided by the AR application. Tourists expressed feeling more involved and helped in understanding the historical narrative of Babad Pasir Luhur. In conclusion, AR technology has the potential to be an effective supporting medium for enhancing the cultural tourism experience while supporting the digital preservation of local history.